The transformations within the film industry in Turkey: "Popcorn Wars", "Netflix" and consumption - GÖZTEPE, MUSTAFA ORHAN (My University, 2020)
Within the last decade, Turkey's film industry has been marked by a growing interest toward domestic productions from its audience. These productions are mostly include big stars from television and produced by a few particularly powerful film production companies. Their genres are extremely limited to comedies and national epics and they are box-office hits each and every year. Turkey's cinema industry faced a major debate in 2019 which is called "Popcorn Wars" On the one side was Turkey's largest film distribution company and the owner of most of the motion picture theaters, Mars Group; on the other side was the three major stars, Cem Yılmaz, Yılmaz Erdoğan, Şahan Gökbakar, as the representatives of the three most powerful film production companies, Kara Komik Filmler, BKM, and Çamaşırhane, owned by each of them. The conflict occurred when the representatives reacted to the decision of Mars Group to increase the ticket prices by including food and beverages. Yılmaz and Gökbakar delayed the release of their films to the second half of the year, with the expectation that a new law regulating film production and distribution would take affect in their favor. Yılmaz Erdoğan and his production company (BKM) decided to follow a different approach by selling the broadcasting rights of his film to Netflix shortly after the release of the film on theathers. Netflix, a new player in the media industries in Turkey, quickly became a new platform that is open to releasing new local productions as well as an alternative that could be used to negotiate with Mars Group. As a result of this conflict, the delaying of the highly expected films and the Netflix element, the first six months of 2019 ticket sales dropped 45,1% and cinema industry in Turkey experienced its biggest decrease in box office revenue in the 2000s. This paper investigates the economic and political discourses that shape Turkey's film industry, by focusing on the entrance of Netflix to Turkey's media industries as a powerhouse that transforms both cinema and television industries, the influence and power of the aforementioned three film production companies, the entrapment of movie theaters within shopping malls and its affects on the consumption habits of audiences, and finally the consequence of Mars Group becoming the monopolizing source of film distribution within the industry.
Keywords: Türkiye; Film Endüstrisi; Film Dağıtımı; Turkey; Film Industry; Film Distributio; Netflix